The change of perception on emigration in the cuban society: The change of perception on emigration in the cuban society - Candela Figueroa, María Fernanda (Cinzontle, 2021)
In this article, we reflect on theway in which in Cuba the perceptionabout the figure of themigrant has changed over theyears, the above taking as a startingpoint the triumph of theRevolution. Through the reviewof various investigations, as wellas literary works, it is analyzedhow the opinion of Cuban societyhas been transformed goingfrom a negative idea to a verypositive one. In the beginning,people who decided to emigratewere seen as enemies of thehomeland, Nowadays they are,in many cases, the economicsupport of family members whoremain on the Island.